Effects of Low Muscle Mass on Albuminuria and Chronic Kidney Disease in Patients With Type 2 Diabetes: The Korean Sarcopenic Obesity Study (KSOS). (12th April 2017) - Chung, Hye Soo; Hwang, Soon Young; Choi, Ju Hee; Lee, Hyun Jung; Yoo, Hye Jin; Seo, Ji-A; Kim, Sin Gon; Kim, Nan Hee; Choi, Dong Seop; Baik, Sei Hyun; Choi, Kyung Mook
Abstract: Background: Previous studies have shown that chronic kidney disease (CKD) is associated with accelerated loss of skeletal muscle in patients on dialysis. However, the relationships of sarcopenia with albuminuria and early-stage CKD in patients with type 2 diabetes have not been examined. Methods: We analyzed diabetic subgroup data from 409 patients with type 2 diabetes from the Korean Sarcopenic Obesity Study (KSOS). Sarcopenia was defined as a skeletal muscle mass index (SMI; SMI [%] = total skeletal muscle mass [kg]/weight [kg] × 100) less than 2 SD below the sex-specific mean for a younger reference group. The estimated glomerular filtration rates and urinary albumin-to-creatinine ratios were used to assess renal function and albuminuria. Results: The prevalence of sarcopenia was significantly increased in the albuminuria group compared with the normo-albuminuria group (26.7% vs 12.6%, p = .001), as well as in CKD 3 group compared with the CKD 1–2 group (46.7% vs 15.1%, p = .005). After adjusting for age, SMI was negatively correlated with urinary albumin-to-creatinine ratios and positively correlated with aspartate aminotransferase, alanine aminotransferase, total cholesterol, high-density lipoprotein cholesterol, and low-density lipoprotein cholesterol levels. Multiple logistic regression analysis revealed that the odds ratio for albuminuria association was 3.02 (95% CI 1.37–6.67) in the lowest tertile of SMI compared with the highest tertile after adjusting for various confounding factors. Conclusions: Sarcopenia is more prevalent in individuals with albuminuria than in those without albuminuria. Furthermore, increased albuminuria is independently associated with low muscle mass in patients with type 2 diabetes.